Operando IR optical control of localized charge carriers in BiVO4 photoanodes - Meng,Z; Pastor,E; Selim,S; Ning,H; Maimaris,M; Kafizas,A; Durrant,JR; Bakulin,AA (Journal of the American Chemical Society, 2023)
In photoelectrochemical cells (PECs) the photon-to-current conversion efficiency is often governed by carrier transport. Most metal oxides used in PECs exhibit thermally activated transport due to charge localization via the formation of polarons or the interaction with defects. This impacts catalysis by restricting the charge accumulation and extraction. To overcome this transport bottleneck nanostructuring, selective doping and photothermal treatments have been employed. Here we demonstrate an alternative approach capable of directly activating localized carriers in bismuth vanadate (BiVO4). We show that IR photons can optically excite localized charges, modulate their kinetics, and enhance the PEC current. Moreover, we track carriers bound to oxygen vacancies and expose their ∼10 ns charge localization, followed by ∼60 μs transport-assisted trapping. Critically, we demonstrate that localization is strongly dependent on the electric field within the device. While optical modulation has still a limited impact on overall PEC performance, we argue it offers a path to control devices on demand and uncover defect-related photophysics.